Effects of DO on N2O emission during biological nitrogen removal using aerobic granular sludge via shortcut simultaneous nitrification and denitrification. Issue 2 (15th January 2020) - Peng, Bo; Liang, Hong; Wang, Shanshan; Gao, Dawen
ABSTRACT: Dissolved oxygen (DO) is an important factor influencing biological nitrogen removal. This study investigated the effects of different DO concentrations (4, 2, 1 mg/L) on nitrous oxide (N2 O) production and nitrogen removal via shortcut simultaneous nitrification and denitrification by aerobic granular sludge (SNDAG ) using a sequencing bath reactor. The results showed that N2 O production was highest (127.6 mg/m 3 ) at a DO concentration of 2 mg/L; this was 24.17 and 2.90 times the production at DO concentrations of 4 and 12 mg/L, respectively. The removal efficiency of total nitrogen also was the highest (61.68%) when the DO concentration was 2 mg/L, compared to 35.22% and 50.65% at DO concentrations of 4 and 1 mg/L, respectively. The efficiency of the SNDAG process reached 53.86% at a DO concentration of 2 mg/L, which was 1.33 and 1.67 times the efficiencies at DO concentrations of 4 and 1 mg/L, respectively. Therefore, reducing the DO concentration benefited the SNDAG process, but increased the emission of N2 O. GRAPHICAL ABSTRACT: